2019
DOI: 10.3390/rs11030219
|View full text |Cite
|
Sign up to set email alerts
|

A Recursive Update Model for Estimating High-Resolution LAI Based on the NARX Neural Network and MODIS Times Series

Abstract: Leaf area index (LAI) remote sensing data products with a high resolution (HR) and long time series are in demand in a wide variety of applications. Compared with long time series LAI products with 1 km resolution, LAI products with high spatial resolution are difficult to acquire because of the lack of remote sensing observations in long-term sequences and the lack of estimation methods applicable to highly variable land-cover types. To address these problems, we proposed a recursive update model to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Verrelst et al [112] compared four machine learning regression algorithms (ANN, SVR, kernel ridge regression (KRR), and GPR) using Sentinel-2 and -3 data for estimating biophysical parameter retrieval and concluded that GPR had the best performance (relative RMSE ≈ 0.2) when compared to the other three methods. Wang et al [113] used a neural network approach to combine HJ-1 CCD, GF-1, Landsat TM, Landsat Enhanced Thematic Mapper Plus (ETM+), and MODIS data, which enabled them to fill in missing data in the Landsat images in order to generate continuous time series (8 days) crop LAI with 30 m resolution (RMSE = 0.30).…”
Section: Empirical Modelsmentioning
confidence: 99%
“…Verrelst et al [112] compared four machine learning regression algorithms (ANN, SVR, kernel ridge regression (KRR), and GPR) using Sentinel-2 and -3 data for estimating biophysical parameter retrieval and concluded that GPR had the best performance (relative RMSE ≈ 0.2) when compared to the other three methods. Wang et al [113] used a neural network approach to combine HJ-1 CCD, GF-1, Landsat TM, Landsat Enhanced Thematic Mapper Plus (ETM+), and MODIS data, which enabled them to fill in missing data in the Landsat images in order to generate continuous time series (8 days) crop LAI with 30 m resolution (RMSE = 0.30).…”
Section: Empirical Modelsmentioning
confidence: 99%
“…Shatnawi and Qdais applied NARX ANN model to simulate and estimate of LST values for the next 10 years using between 2000 and 2006 data (Shatnawi and Qdais 2019). The results of another study show that the NARX model is very successful and has very strong fault tolerance capability in LAI time series estimation based on MODIS data (Wang et al 2019). Although NARX ANN is a reliable and successful method for estimating nonlinear data, it is possible to increase the estimation success by developing hybrid methods (Alves and Lopes 2017).…”
Section: Introductionmentioning
confidence: 99%